Worth the Hype? The Relevance of Paid-For Analyst Research for the Buy-and-Hold Investor - Billings, Bruce K.; Buslepp, William L.; Huston, G. Ryan (The Accounting Review, 2014)
ABSTRACT The SEC Advisory Committee on Smaller Public Companies recommends paid-for research to fill the void created by declining sell-side coverage. Potential conflicts of interest inherent in paid-for research challenge this recommendation. We evaluate whether paid-for research provides value to investors or merely reflects hype. Analyses of one- and two-year-ahead paid-for earnings forecasts fail to identify significant bias. Using a portfolio approach, favorable (unfavorable) paid-for recommendations yield positive (negative) stock returns at release, with upward (downward) drift over the following year. Regressing future stock returns on recommendations and valuation estimates using paid-for analysts' forecasts yields similar results. Further, results fail to indicate significant differences in paid-for and matched sell-side research. Overall, our evidence suggests that paid-for research provides relevant information for the buy-and-hold investor that is comparable to that of matched sell-side research, providing empirical support for the SEC Advisory Committee recommendation. JEL Classifications: G11; G14; G24. Data Availability: Data are publicly available from the sources identified in the text.